Human Rights Aspect on Natural Resources Issue in Indonesia - Arifin, Ridwan (Law Research Review Quarterly, 2015)
Natural Resources in Indonesia is one of the important things, not only on a national scale but also internationally. Various aspects of law are closely related to natural resource issues, one of which is human rights issues. This research discusses various aspects of human rights related to natural resource issues in Indonesia.